Freeze-Dried Powder of Fermented Chili Paste—New Approach to Cured Salami Production - Adriana Păucean; Csaba Balázs Kádár; Elemér Simon; Dan Cristian Vodnar; Floricuța Ranga; Iulian Eugen Rusu; Vasile-Gheorghe Vișan; Sonia-Ancuța Socaci; Simona Man; Maria Simona Chiș; Anamaria Pop; Anda E. Tanislav; et al. (Foods, 2022)
Fermented chili powders were obtained through the freeze-drying of fermented chili pastes and used as a condiment, acidifier, antioxidant, colorant, and microbial starter carrier in fermented salami production. Fermented chili powders were examined regarding carbohydrates, organic acids, vitamin C, phenolic compounds, carotenoids, and aroma profile. High concentrations of lactic (10.57–12.20%) and acetic acids (3.39–4.10%) were recorded. Vitamin C content was identified in the range of 398–1107 mg/100 g, with maximum values for C. annuum cv. Cayenne chili powder. Phenolic compounds showed values between 302–771 mg/100 g. Total carotenoid content was identified between 544–2462 µg/g, with high concentrations of capsanthin esters. Aroma profile analysis evidenced specific compounds (1-hexanol, 2-hexanol, hexenal, E-2-hexenal) with sensory importance and a more complex spectrum for Capsicum chinense cultivar. Plant-specific lactic acid bacteria showed dominance both in fermented chili paste, chili powder, and salami. Lactic and acetic acids from the fermented chili powder reduced the pH of the filling immediately, having a stabilizing effect on the meat. Nor molds or pathogens were identified in outer limits. Based on these results, fermented chili powders could be used as starter carriers in the production of fermented meat products for exceptional sensory properties and food safety management.